The Effect of Land Crane Maintenance and Land Crane Operators on Scheduling and its Implications on Operational Safety of Loading and Unloading at PT Samudera Maritime Indonesia - Riyanto, Firdania Amelia; Cahyadi, Tri; Herawati, Susi (Dinasti International Journal of Digital Business Management, 2025)
Operational safety in cargo loading and unloading activities at Jetty Nusantara is greatly influenced by the effectiveness of scheduling land crane usage, which depends on two main factors: land crane maintenance and land crane operator skills. Several issues often encountered, such as reliance on designated cargo handling (PBM) parties, unexpected breakdowns of land cranes, and insufficient operator skills in crane operations, can affect operational safety. Poorly managed scheduling also worsens operational conditions, leading to fatigue, equipment damage, and an increased risk of workplace accidents. This study aims to analyze the impact of land crane maintenance and land crane operator skills on scheduling crane usage and its impact on operational safety in cargo loading and unloading at PT Samudera Maritime Indonesia. Using a quantitative approach and cross-sectional design, this study involved 70 respondents selected using the Slovin formula. The collected data were analyzed using SmartPLS software. The results of the study show that land crane maintenance and land crane operator skills have a positive and significant effect on scheduling crane usage and operational safety in cargo loading and unloading. The findings indicate that quality training and adequate training facilities can enhance employees' ability to manage risks and improve their performance. Effective scheduling also contributes to improved operational safety. The recommendations from this study are for PT Samudera Maritime Indonesia to continue improving land crane maintenance and the quality of training to support operational safety in the future.